ANALISIS KESULITAN BELAJAR SISWA MENTAL RETARDATION DI SDN KEDUNGPUTRI 2 (Studi Kasus di SDN Kedungputri 2, Paron Kabupaten Ngawi) - Candra Dewi, Melik Budiarti dan (Universitas Muhammadiyah Ponorogo, 2017)
This study entitled Analysis of Reading Difficulties in Mental Retardation Students In Primary School (Case Study In SDN Kedungputri 2). The background of this research is the emergence of learning problems in mentally retarded children attending regular elementary school (not designated as inclusive primary). This study aims to find out the learning process, especially learning to read mental retardation children in SDN Kedungputri 2, Paron, Ngawi and to find out the steps taken in overcoming the difficulties of reading children mental retardation in SDN Kedungputri 2, Paron, Ngawi. This research is descriptive qualitative research. The data collected in this research are facts and information on the implementation of character education of discipline in elementary school. In this study the data source is teachers and students. Data collection techniques used in this study consist of (a) observation, (b) interview, and (c) test. In this study the validity of the data using data triangulation. Data analysis technique is done by using interactive data model analysis technique. Based on the data collected can be seen that students who experience mental retardation initials AS and the students have difficulty reading. Teachers continue to pay attention to the difficulties of learning to read the beginning to the AS.